2012
DOI: 10.1177/1049732312467706
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Risks in the Local Workforce Engaged in Disaster Relief and Reconstruction

Abstract: To build a sustainable workforce for long-term disaster relief and reconstruction, more effort must be made to promote local relief workers' mental health. We conducted 25 semistructured interviews with local relief officials 10 months after the 2008 earthquake in China to investigate the stress and coping experiences in their personal lives as survivors. We conducted thematic analysis of interview transcripts. Traumatic bereavement and grief, housing and financial difficulties, and work-family conflict were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Incidentally, several past studies focusing on stress among relief workers revealed that female sex and traumatic bereavement can be predictors of developing PTSD or depression after community disasters. In the present study, the PR of the participants who experienced bereavement was high at 1.73, similar to the results of previous studies . Financial losses and damage to the home have also been shown to be associated with subsequent mental health problems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Incidentally, several past studies focusing on stress among relief workers revealed that female sex and traumatic bereavement can be predictors of developing PTSD or depression after community disasters. In the present study, the PR of the participants who experienced bereavement was high at 1.73, similar to the results of previous studies . Financial losses and damage to the home have also been shown to be associated with subsequent mental health problems.…”
Section: Discussionsupporting
confidence: 90%
“…The most likely reason for the lack of significant differences in the other variables is beta error, as the number of participants was too low. Incidentally, several past studies focusing on stress among relief workers revealed that female sex and traumatic bereavement can be predictors of developing PTSD or depression after community disasters. In the present study, the PR of the participants who experienced bereavement was high at 1.73, similar to the results of previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…Wen, Shi, Li, Yuan, & Wang, 2012). Another study eminent that feeling connected might be important for recovery from mass trauma and post-traumatic intensification in local relief workers (X. L. Wang, Chan, Shi, & Wang, 2013). Therefore, measures to promote communication ultimately increase sharing of worst insight traumatic feelings and fear of disaster at the community level, this might smooth the progress of psychological recovery in general population.…”
Section: Discussionmentioning
confidence: 99%
“…Many participants viewed the experience as rewarding, in terms of feeling they had made a contribution; personal accomplishment; and consequent improved confidence and self-esteem, increased compassion, and re-evaluation of the self and meaning of life Soliman et al, 1998;Wang et al, 2013;Yang et al, 2010). Humanitarian concern, work satisfaction and the feeling of ''giving back'' were motivators.…”
Section: Personal and Professional Growthmentioning
confidence: 99%
“…McCormack & Joseph (2013),,Stuhlmiller (1994),Wang et al (2011Wang et al ( , 2013, and Wyche et al(2011) Chang et al (2008), Curling & Simmons (2010), Huang et al (2013), Karanci & Acarturk (2005), Miles et al (1984), Paton (1994), Wilkinson (1983), and Wyche et al (2011) Formal post-disaster support: Peer support/Professional support/Counselling/ Debriefing Bakhshi et al (2014), Bjerneld et al (2004), Hearns & Deeny (2007), McCormack & Joseph (2013) and Stuhlmiller (1994) Durham et al (1985), Kenardy et al (1996), Van der Velden et al (2012) and Wu et al (2012) Media: Media coverage of disaster/ Publicity Bakhshi et al (2014), Norris et al (2005) Miles et al (1984), Nishi et al (2012), and Paton (1994) (continued )…”
mentioning
confidence: 99%